Pengembangan Media Pembelajaran Powtoon Berbasis Critical Thinking Skill Pada Sub Tema "Manfaat Energi" Kelas IV Sekolah Dasar - Muhammad Ferdian Syaifullah Jasadi; Titi Anjarini; Nurhidayati Nurhidayati (Dharmas Education Journal (DE_Journal), 2021)
The process of interaction between teachers and students is called learning. Elementary school in Indonesia is the most basic level of education. The education system in Indonesia is governed by the curriculum. Currently the curriculum applied is the 2013 curriculum. Unlike the previous curriculum, the 2013 curriculum combines several subjects into one including science learning. In its application, learning science requires learning media. Learning media is divided into two types, namely conventional and modern. One of the modern learning media is Powtoon learning media. To maximize the use of Powtoon, it is combined with aspects of critical thingking skills. This study aims to (1) determine the development of Powtoon media, (2) determine the feasibility of Powtoon media, and (3) determine the practicality of Powtoon media. The research method used is Research and Development. The development model of this research is the ADDIE model which includes analysis, design, development, implementation, and evaluation. The results of this study: (1) produced a product in the form of Powtoon media based on critical thining skills, (2) the results of the feasibility of Powtoon media based on critical thinking skills got an average of 3.6 so that it was categorized as very feasible. (3) the practicality of Powtoon media based on critical thinking skills seen from the responses of students at the broad trial stage got a percentage of 92% so it was categorized as very practical. And the results of the extensive trial evaluation get a percentage of 91.6% so it is categorized as very practical.